Non-Canonical Hh Signaling in Cancer—Current Understanding and Future Directions - Gu, Dongsheng (Cancers (Basel), 2015)
As a major regulatory pathway for embryonic development and tissue patterning, hedgehog signaling is not active in most adult tissues, but is reactivated in a number of human cancer types. A major milestone in hedgehog signaling in cancer is the Food and Drug Administration (FDA) approval of a smoothened inhibitor Vismodegib for treatment of basal cell carcinomas. Vismodegib can block ligand-mediated hedgehog signaling, but numerous additional clinical trials have failed to show significant improvements in cancer patients. Amounting evidence indicate that ligand-independent hedgehog signaling plays an essential role in cancer. Ligand-independent hedgehog signaling, also named non-canonical hedgehog signaling, generally is not sensitive to smoothened inhibitors. What we know about non-canonical hedgehog signaling in cancer, and how should we prevent its activation? In this review, we will summarize recent development of non-canonical hedgehog signaling in cancer, and will discuss potential ways to prevent this type of hedgehog signaling.